Revealing the different effects of VIB transition metals X (X = Cr, Mo, W) on the electrochemical performance of Li-rich cathode Li2MnO3 by first-principles calculations. Issue 40 (5th October 2022) - Zhang, Shiwei; Wang, Jianchuan; Liu, Huan; Zhang, Weibin; Sun, Lixian; Du, Yong; Seifert, Hans J.; Lei, Ting
Abstract : The doping of Cr, Mo and W enhances the electrochemical activity of Li2 MnO3 via different charge compensation mechanisms. A summary of the variations of charge compensation mechanisms facilitates the rapid design of Li-rich cathodes. Abstract : Transition metal (TM) doping is widely applied to optimize the electrochemical performance of Li2 MnO3, a promising cathode material of next-generation Li-ion batteries. The effect of doping on the performance of Li2 MnO3 can vary with the elemental period of the doped TM. However, the rules of the different effects have not been well summarized, especially for TM elements within the same group. In this work, the effects of TM element (Cr, Mo, and W in group VIB) dilute doping on the electrochemical performance of Li2 MnO3 are investigated through first-principles calculations. The results show that Mo and W can induce more obvious local lattice distortion. Although Cr, Mo and W doping can improve the electrochemical activity of Li2 MnO3, they modify the charge compensation mechanism in different ways. At the initial stage of delithiation, both Cr and O undergo significant oxidation, and Mo can act as the main oxidation center, while W can trigger the electrochemical activity of Mn around it. The O ions around Mo and W are more stable during the delithiation due to the mild oxidation and the strong bonding of Mo–O and W–O. Furthermore, Cr, Mo and W dilute doping can promote the interlayer diffusion of Li at the initial charging state, which is gradually enhanced with the increase of the period of the doped elements, but Mo and W doping would hinder the intralayer diffusion of Li near the doping sites during further delithiation process. Our results highlight the difference in the effects of TM (in the same group) doping on the performance of Li2 MnO3 and would facilitate fast and good design of Li-rich cathodes.